Environmental Conservation and Use of Economic Incentives to Conserve Biological Resources in Nigeria - Edame, Greg Ekpung (International Journal of Sustainable Energy and Environmental Research, 2014)
This paper analyzes environmental conservation and use of economic incentives to conserve biological resources in Nigeria. Conservation refers to the management of human use of the biosphere so that it may yield the greatest sustainable benefit to present generations while maintaining its potential to meet the needs and aspirations of future generations. Its compliments are preservation, maintenance, sustainable utilization, restoration and enhancement of the natural environment. It is concerned with plants, animals, microbes, and with the non-living elements of the eco-systems which sustain them. The varieties of ecological system in Nigeria create an endowment of biological resources of which the nation is justifiably proud of. The conservation of these resources for the benefits of the present and future generations has been practiced with little attention given to develop a crop specialist (ecologists) to handle the subject. Under this situation the urgency of conservation programmes can no longer be denied. The establishment of the National Resources Conservation Council by the Nigerian Government is a welcome idea. Working together, it should be possible to achieve the goal of conservation namely that human survival and sustainable economic development depend fundamentally on proper maintenance of renewable resources; vegetation and forest, water, marine and fisheries resources as well as wild animals and soil resources. The paper finally looks at the values of biological resources, the cost of protecting biological resources and the status of conservation practices.